Bituminous pavement sustainability improvement strategies - Toryila Michael Tiza; Onyebuchi Mogbo; Sitesh Kumar Singh; Nagaraju Shaik; Mahesh P. Shettar (Energy Nexus, 2022)
Transportation systems have enormous challenges in terms of sustainability since they deal with issues like economic, environmental, and social factors, and pavement sustainability is unavoidably one of these problems. This study investigates pavements' sustainability potential, and in doing so, it looks at both global practices and personal experiences. This research investigates the long-term viability of pavements. Some of the topics covered in this course are: Recycled Concrete, Recycled Asphalt Pavement, Bio-binders of asphalt, asphalt cement, warm mix asphalt, tack coat, rubberized asphalt (RA), polymer modified asphalt (PMA), and sustainability in pavement design. According to the findings, research is needed to provide environmental sustainability training, including preservation and maintenance solutions. Carbon sequestration and resource regeneration are environmental sustainability elements that need to be considered when selecting treatment options for pavement preservation. Recycled or alternative materials must be found for pavement preservation and maintenance techniques. Finally, research is urgently needed to assess the environmental advantages of asphalt crack sealing. It is thus imperative that any new studies on pavement incorporate sustainable pavement management components.